IL‐23 modulates histamine‐evoked itch and responses of pruriceptors in mice. Issue 12 (19th October 2020) - Pavlenko, Darya; Funahashi, Hideki; Sakai, Kent; Hashimoto, Takashi; Lozada, Taisa; Yosipovitch, Gil; Akiyama, Tasuku
Abstract: Accumulating evidence has highlighted the essential roles of cytokines in itch processing. Although IL‐23 and Th17 cytokines are elevated in inflammatory skin disorders, their role in itch is unknown. Here, we investigated the role of IL‐23 and IL‐17A in itch response using an in vitro calcium imaging of mouse dorsal root ganglion (DRG) neurons and an in vivo behaviour test. Calcium imaging studies revealed that a few DRG neurons (~5%) responded to either IL‐23 or IL‐17A. Pretreatment cells with IL‐23 significantly reduced calcium responses to histamine and capsaicin but not chloroquine. Behaviour experiments showed neither IL‐23 nor IL‐17A evoked scratching. IL‐23 significantly decreased histamine‐evoked scratching without affecting chloroquine‐evoked scratching. There was no difference in scratching between IL‐17A‐ and vehicle‐treated groups. These results indicate that IL‐23 might play a role in regulating histaminergic itch via modulation of TRPV1 activity.